The Effectiveness of Acupuncture for Pain Relief in Knee Osteoarthritis Patients in Khaokho Hospital, Phetchabun Province - Phongchamnaphai, Phana (Journal of Health Science of Thailand, 2018)
The purpose of this quasi-experimental study was to measure the level of pain reduction that came from non-electroacupuncture on knee osteoarthritis patients in Khaokho hospital,PhetchabunProvinceduring October 2005-September 2007. Samples of 49 cases were collected from out-patients in both sex aged fifty years and over who had had chronic pain for at least 6 months due to knee osteoarthritis diagnosed from American Collage of Rheumatology (ACR) clinical criteria. The samples had no experience in acupuncture and no contraindication for acupuncture treatment. The visual analog pain scale (VAS) were collected and the patients evaluated the pain by themselves before acupuncture treatment and after the 2nd, 5th and 8th visits. Statistical comparison of therapeutic results were made by using paired t-test. The study showed that after applying acupuncture treatment after the 2nd, 5th and 8th visits, the pain reduction experiences compared with those before acupuncture was statistical significant in both male and female and all age groups. In conclusion, acupuncture is an effective on pain relief for patients with knee osteoarthritis.